Water Consumption and Environmental Impact of Multifamily Residential Buildings: A Life Cycle Assessment Study - Mehzabeen Mannan (16442001) (2022)
Water use in buildings accounts for a large share in global freshwater consumption where research on the impacts of life cycle water use receive little or no attention. Moreover, there is very limited knowledge regarding such impacts that focus on the life cycle emissions from water consumption in building environments in the world’s most water-stressed countries. Hence, this study attempted to quantify the environmental impacts of operational water use in a multi-family residential building through a life cycle assessment (LCA). A small part of a Middle Eastern country, Doha (Qatar), has been selected for the primary assessment, while water-use impact in Miami (Florida) was chosen as a second case study, as both locations fall into similar climate zone according to ASHRAE Climate Zone Map. The LCA score indicated much higher impacts in the Doha case study compared to Miami. The variation in the result is mainly attributed to the raw water treatment stage in Doha, which involves energy-intensive thermal desalination. Again, relative comparison of the annual water and electricity use impacts for the modeled building was performed at the final stage for both locations. Water use was attributable for 18% of the environmental impacts in Miami, while this value increased to 35% in Doha. This initial assembled LCA result will be beneficial to both water authorities and building research communities in establishing more sustainable water use policies for specific regions/countries that will ultimately benefit the overall building environment. Other Information Published in: Buildings License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/buildings12010048